The Correlation between Mothers' Breastfeeding Pattern and Stunting among Toddlers - Tiffatul Jannah Firdausya; Deisy Sri Hardini (Universitas Airlangga, 2020)
Introduction: Stunting is a condition of the measured height of toddlers, which is less to the age. Stunting, which occurs in these children, is also considered in chronic nutrition problems. The study aimed to discover the correlation between breastfeeding mothers' pattern in breastfeeding for toddlers aged 0 days to 6 months with the stunting incidence in toddlers in Gandatapa village, Sumbang sub-district, Banyumas district.Methods: This study implemented an observational analytic method that examined the correlation between breastfeeding mothers' patterns and stunting incidence. This research design was case control. This study conducted two sampling techniques; total sampling and simple random sampling, and each was used for sampling and control groups. The research sample collected 80 respondents. The study used a questionnaire of breastfeeding mothers and TB/U observation charts for ages 2 to 5 years, according to WHO 2005.Results: Based on the bivariate analysis, the pattern of breastfeeding mothers in Gandatapa Village, Sumbang District, Banyumas Regency was in a bad category with 22 stunting toddlers (55%). Pearson Chi-Square test on the Pattern of Breastfeeding Mothers towards Stunting Incidents in toddlers obtained p-value = 0.024 <0.05 with an OR value of 2.852 (95% CI 1.137 - 7.152).Conclusion: Toddlers under 24 to 35 months can increase the risk of stunting incidence when mothers have poor breastfeeding patterns.